2015
DOI: 10.17221/101/2014-pps
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activities of extracts of three lichen species on Sitophilus granarius (L.) (Coleoptera: Curculionidae)

Abstract: Emsen B., Yildirim E., Aslan A. (2015): Insecticidal activities of extracts of three lichen species on Sitophilus granarius (L.) (Coleoptera: Curculionidae). Plant Protect. Sci., 51: 155-161.Four different concentrations of extracts obtained from three lichen species (Lecanora muralis (Schreb.) Rabenh., Letharia vulpina (L.) Hue, and Peltigera rufescens (Weiss) Humb) were tested against adults of Sitophilus granarius (L.) in Petri dishes. After treatments, mortalities of the adults were determined after 24, 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Rabenh. and Peltigera rufescens (Weiss) Humb revealed other lichen species that was effective on S. granarius (Emsen et al, 2015). In that study where concentration-dependent insecticidal activity was observed, median lethal concentration (LC 50 ) values of L. vulpina, L. muralis and P. rufescens were 0.51, 0.67 and 0.33, respectively.…”
Section: Insecticidal Efficacies Of Lichensmentioning
confidence: 89%
“…Rabenh. and Peltigera rufescens (Weiss) Humb revealed other lichen species that was effective on S. granarius (Emsen et al, 2015). In that study where concentration-dependent insecticidal activity was observed, median lethal concentration (LC 50 ) values of L. vulpina, L. muralis and P. rufescens were 0.51, 0.67 and 0.33, respectively.…”
Section: Insecticidal Efficacies Of Lichensmentioning
confidence: 89%
“…Based on this, some studies demonstrated that the toxicity of extracts isolated from lichen samples against pests was related to their components (Emmerich et al, 1993;Balaji et al, 2007;Cetin et al, 2008). Extracts isolated from different lichen species might have different toxicity levels, which can be attributed to their different chemical composition (Sahip et al 2008;Yildirim et al 2012;Emsen et al 2015). Therefore, lichens can be potential sources of natural compounds for pest management.…”
Section: Discussionmentioning
confidence: 99%
“…Diseases such as malaria, dengue, yellow fever, Japanese encephalitis, chikungunya, and filariasis are transmitted through mosquito vectors. Hence, control of insects is a key factor in the management of crop loss and in the prevention of human diseases that are transmitted through insect vectors (Chen and Wilson, 2005;Dar and Wani, 2010;Ghaly and Edwards, 2011;Oberemok et al, 2015;Ricci et al, 2012;Singh et al, 2015;Verma et al, 2009). The management of these insect pests is commonly achieved using synthetic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms (such as bacteria, fungi, and viruses) and natural products including lichens and their metabolites appear to be promising as biopesticides. Biopesticides can replace, at least in part, few of the hazardous chemical agents when used in integrated pest management approaches (Cetin et al, 2008;Ghosh et al, 2012;Gupta and Dikshit, 2010;Kumar, 2012;Nanayakkara et al, 2005;Oliveira et al, 2014;Patel et al, 2016;Ramanujam et al, 2014;Rodriguez-Saona et al, 2016;Verma et al, 2009;Vijayakumar et al, 2010). In this review, a detailed literature survey was carried out to compile information available on the insecticidal activity of lichens and lichen metabolites by referring journals and search engines such as Google Scholar, PubMed, and ScienceDirect.…”
Section: Introductionmentioning
confidence: 99%